Modelling the insulin signaling pathway and glucose transport induction in differentiated 3T3-L1 mouse adipocytes - Myburgh, Lauren (Stellenbosch : Stellenbosch University, 2021)
Thesis (MSc)--Stellenbosch University, 2021.